1992
DOI: 10.1136/oem.49.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and other environmental factors and multiple myeloma: a population based case-control study.

Abstract: Epidemiological studies on the aetiology of multiple myeloma are reviewed as a background to this population based case-control study performed in an area with a high incidence of multiple myeloma. The purpose was to identify and evaluate several suspected environmental factors in relation to this disease. A total of275 confirmed cases diagnosed in four counties in northern Sweden during four years were compared with the same number of control subjects drawn from population registries. The controls were matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 55 publications
4
75
2
Order By: Relevance
“…species of farm animals was found (Eriksson and Karlsson, 1992). A UK study found an OR of 1.69 for exposure to farm animals , although the number of exposed cases was few (Staines and Cartwright, 1993).…”
mentioning
confidence: 98%
“…species of farm animals was found (Eriksson and Karlsson, 1992). A UK study found an OR of 1.69 for exposure to farm animals , although the number of exposed cases was few (Staines and Cartwright, 1993).…”
mentioning
confidence: 98%
“…[4][5][6] The increase in these hematologic neoplasias is presently not understood, although some risk factors are being discussed intensively. They involve agricultural occupations [7][8][9][10][11][12] and contact with cattle. [13][14][15][16][17][18] Several authors also report an elevated risk for these neoplasms in butchers, abattoir workers and meat cutters.…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…From these, 18 were excluded because they did not provide enough data to calculate the outcome, were already included in other studies, or did not focus on PCM or smoking. From these 17 studies, 4 were prospective cohort [5-8] and 13 were case-control studies [9][10][11][12][13][14][15][16][17][18][19][20][21]. The prospective studies were published between 1990 and 2007, and included 1,232 cases identified in a total cohort of 789,000 individuals.…”
mentioning
confidence: 99%